2022
DOI: 10.2176/nmc.oa.2021-0203
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up Results after Flow Diverter Therapy Using the Pipeline Embolization Device for Large or Giant Unruptured Internal Carotid Artery Aneurysms: Single-center Retrospective Analysis in the Japanese Population

Abstract: Flow diverter (FD) therapy using Pipeline embolization device (PED) has become an important alternative to treat internal carotid artery (ICA) aneurysms. Herein, we report the long-term outcome for 3 years after FD therapy using PED for ICA aneurysms in Japan. The patients who underwent angiographical and/or clinical follow-up for 3 years after the FD therapy using PED of large or giant unruptured ICA aneurysms from December 2012 at our university hospital are the subjects of this study. We retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…Fujii et al reported that elderly patients were a risk factor of poor aneurysm occlusion with the PED. 5 ) In the present series, nine patients 65 years or older had a low CO rate (33.3%). On the other hand, 11 patients younger than 65 years had a high CO rate (81.8%).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Fujii et al reported that elderly patients were a risk factor of poor aneurysm occlusion with the PED. 5 ) In the present series, nine patients 65 years or older had a low CO rate (33.3%). On the other hand, 11 patients younger than 65 years had a high CO rate (81.8%).…”
Section: Discussionsupporting
confidence: 42%
“…Recently, flow diverter (FD) therapy has become an important alternative endovascular strategy for large or giant unruptured intracranial aneurysms. [2][3][4][5] Although various FDs made of different materials and with different delivery systems are available worldwide, there are currently three commercially available flow diverters in Japan, namely, the Pipeline Flex (Medtronic, New York, NY, USA), the FRED (Terumo, Tokyo, Japan), and the Surpass Streamline (SS) (Stryker, Tokyo, Japan). The SS is the newest in Japan that was most recently approved in January 2021.…”
Section: Introductionmentioning
confidence: 99%
“…After 12 months, this proportion decreased slightly because of symptom worsening in two patients with a partially occluded aneurysm that had recurred or enlarged. Previous studies have reported that the occlusion rate increases over the first 12 months in aneurysms treated using flow diversion, but not much after that time 18 19. Considering all the above, additional treatment may be advisable for patients treated with flow diversion who do not experience improvement in cranial neuropathy and aneurysm occlusion within the first 12 months of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Literature search was performed on March 21, 2022. After removal of duplicates and screening of titles and abstracts, we sought for the original articles of 82 publications 7 13–93. After completion of literature review and data extraction and before closing the database, the literature search was repeated on PubMed only on May 22, 2022, using the above-mentioned search string to identify additional potentially eligible articles.…”
Section: Resultsmentioning
confidence: 99%